Column design with semi-rigid end frame - Wan Jusoh, Wan Hidayatul Hak (2010)
The strength and the stability of the steel frames is mostly influenced by the connection strength and stiffness. Usually in conventional analysis, the convenient and easy way to design the connection is by using pin or rigid connection. But, in actual the connection is behaved most likely between these two (2) connections. The connection called semi-rigid which possessed a certain degree of rotational restraint. Years ago, numerous studies have been conducted to investigate the behavior of column and developed the design method on semi-rigid connection for braced and unbraced frames. However, semi-rigid connection has not been adopted very enthusiastically by the structural designer due to the lack of confidence about it behavior. They are convenient in using the conventional design method based on BS 5950 [1], Eurocode [2, 3] or AISC. Recently there was a study which proposed the easy way to design column which neglect moment transfer to column known as simplified apin approach [4, 5]. This study is conducted to look into the column at ultimate limit state with the aid of computer software name LUSAS Analyst and to look the reliability of simplified apin approach as a straightforward method compared to conventional design. From the result of this study, it found that the column strength is affected by the stiffness of the connection and the simplified apin approach also reliable to use in design the column without transferring the moment. The value of apin always give more than unity which mean it is reliable.